Spectroscopic, Anticancer and Theoretical Study of New Ligand Derived From (3-hydrazineylidenebutan-2-one oxime) and its Complex with Some Metal Ions: Spektroskopi, Antikanker dan Kajian Teoritis Ligan Baru yang Berasal dari (3-hidrazinilidenebutan-2-satu oksim) dan Kompleksnya dengan Beberapa Ion Logam - Abbas, Israa Ali; Neamah, Fayez Owaid Neamah2 (Universitas Muhammadiyah Sidoarjo, 2024)
The new Schiff base ligand derivate from 3-hydrazineylidenebutan-2-one oxime and its metal complexes were synthesized and characterized by analytical technique and spectroscopy method such as HNMR, FTIR and mass spectroscopy. The optimized geometric structures and HOMO-LUMO orbitals were computed by using DFT (density functional theory) at B3LYP/6-31G+(d,p) level. When the ligand's cytotoxic activity was tested against human breast cancer (MCF-7) and normal cells (WRL68), it was found to be more cytotoxic against MCF-7 but reasonably safe against normal cells. Highlights: ynthesis: Schiff base ligand and metal complexes characterized via spectroscopy techniques. Computational: DFT calculated optimized structures, HOMO-LUMO orbitals at B3LYP/6-31G+ level. Cytotoxicity: Ligand showed higher toxicity against MCF-7 cells, safe for normal cells. Keywords: anticancer, complex, ligand, oxime, Schiff base